Hand-rim biomechanics during geared manual wheelchair propulsion over different ground conditions in individuals with spinal cord injury - Jahanian, O.; Gaglio, A.; Cho, C. C.; Muqeet, V.; Smith, R.; Morrow, M. M. B.; Hsiao-Wecksler, E. T.; Slavens, B. A. (Journal of Biomechanics, 2022)
Geared manual wheelchair wheels, a recently developed alternative propulsion mechanism, have the potential to alleviate the high upper extremity demands required for wheelchair propulsion and help decrease the risk of secondary injuries in manual wheelchair users. The objective of this study was to investigate the effects of using geared manual wheelchairs on hand-rim biomechanics of wheelchair propulsion in individuals with spinal cord injury (SCI). Seven manual wheelchair users with SCI propelled their wheelchairs equipped with geared wheels over tile, carpet, and up a ramp in low gear (gear ratio 1.5:1) and standard gear (gear ratio 1:1) conditions. Hand-rim kinetics and stroke cycle characteristics were measured using a custom instrumented geared wheel. Using the geared wheels in the low gear condition, propulsion speed (P = 0.013), peak resultant force (P = 0.005), peak propulsive moment (P < 0.006), and peak rate of rise of the resultant force (P = 0.035) decreased significantly in comparison with the standard gear condition. The significant increase in the number of stroke cycles when normalized to distance (P = 0.004) and decrease in the normalized integrated moment (P = 0.030) indicated that although a higher number of stroke cycles are required for travelling a given distance in the low gear than the standard gear condition, the low gear condition might be less demanding for the upper extremity. These results suggest that geared wheels could be a useful technology for manual wheelchair users to independently accomplish strenuous propulsion tasks including mobility on carpeted floors and ramp ascension, while reducing the risk factors contributing to the incidence of secondary upper extremity injuries.